The Big Book of Flight - White, Rowland (London Bantam Press, 2014)
Everybody dreams of flying. For as long as we've been able to look up and see the birds we've wanted to join them. But our efforts to do so have not always been as elegant or accomplished. Instead, there's been danger, excitement, courage and brilliance. The Big Book of Flight is a celebration of it all, and a lot more besides, packed with derring-do stories of aviation's pioneers as well as fascinating profiles of remarkable planes, from Spitfires to Space Shuttles (and a number of other wondrous projects that never quite got off the drawing board). Along with a unique collection of fantastic flight trivia, crucial questions are also addressed: What's so scary about the Bermuda Triangle? Why does airline food taste so bad? And how do you make the perfect paper dart? With stunning photographs and illustrations throughout, The Big Book of Flight promises to surprise, entertain and fire the imaginations of anyone with their head in the clouds
Include Color Illustration
Keywords: Aeronautics -- Flight -- Flying-machines